دور معلمي الحلقة الأولى في تنشيط الذكاءات المتعددة للتلامذة دراسة ميدانية في محافظة اللاذقية - جناد روعة عارف; موسى وداع علي (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدفت هذه الدراسة بدايةً إلى الكشف عن دور معلمي الحلقة الأولى في تنشيط الذكاءات المتعددة للتلامذة؛ من خلال استخدام أنشطة متنوعة مناسبة لكل ذكاء من الذكاءات السبعة التي حددها جاردنر ، كما هدفت أيضاً إلى تحديد نوعي الذكاء اللذين يلقيان الاهتمام الأكبر والأقل من قبل معلمي الحلقة الأولى، وتعرف تأثير سنوات الخبرة في التعليم على استخدامهم لأنشطة ذكاء ما دون سواه. ووفقاً لذلك تم الاعتماد على المنهج الوصفي ؛ إذ صُممت استبانة خاصة لهذا الغرض تضمنت( 42) بنداً موزعة على سبعة محاور. وتم توزيع الاستبانة على عينة عشوائية بلغ عددها( 132) معلماً ومعلمةً من حملة الإجازة في التربية اختصاص معلم صف. وقد أظهرت الدراسة إيجابية الدور الذي يلعبه المعلمون في تنشيط الذكاءات المتعددة لتلامذتهم بشكل عام، وقد حصل الذكاء الاجتماعي على الاهتمام الأكبر يليه الذكاء الشخصي، والمنطقي، والحركي، والمكاني، والموسيقي، واللغوي. بينما لم تُظهر الدراسة أية فروق بين متوسطات درجات المعلمين وذلك في تنشيط الذكاءات المتعددة تبعاً لمتغير سنوات الخبرة في التعليم. وقد أوصت الدراسة بإقامة دورات تدريبية لمعلمي الحلقة الأولى القائمين على رأس عملهم بغرض تعريفهم بنظرية الذكاءات المتعددة وتطبيقاتها في المجال التربوي، وتضمين المناهج الدراسية نشاطات مناسبة لهذه النظرية. This study aimed to explore the role of the teachers of basic teaching stage in activating the Multiple Intelligences of Pupils , by using variety and appropriate activities for each sort of intelligence from the seven Intelligences that Gardner has set. It also aimed to determine the two sorts of intelligence that get the most and the least interest by the teachers of basic teaching stage , and discovering the impact of the years of experience in teaching on their using intelligence activities alone. According to that, the descriptive approach was adhered. So a special questionnaire- consisted of( 42) items in seven fields was designed for that purpose. The sample of this research was selected randomly and consisted of( 132) teachers who have a licence in education (class room teacher). The research’s results show the positive role of the teachers of basic teaching stage in motivating the Multiple Intelligences of their pupils in general. The interpersonal intelligence has got the greatest interest , then intrapersonal, logical- mathematical, bodily- kinesthetic, spatial, musical, and linguistic intelligence. Whereas the study doesn’t shows any statistical differences among the average of the degrees of teachers in activating multiple intelligences according to the years of experience in teaching. This study recommended to establish training sessions to the teachers of basic teaching stage to educate them of the multiple intelligence theory and its applications in education, and to include the curricula suitable activities of this theory.